Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1103/physreva.92.043412
|View full text |Cite
|
Sign up to set email alerts
|

Quantum interference in the field ionization of Rydberg atoms

Abstract: We excite ultracold rubidium atoms in a magneto-optical trap to a coherent superposition of the three |m j | sublevels of the 37d 5/2 Rydberg state. After some delay, during which the relative phases of the superposition components can evolve, we apply an electric field pulse to ionize the Rydberg electron and send it to a detector. The electron traverses many avoided crossings in the Stark levels as it ionizes. The net effect of the transitions at these crossings is to mix the amplitudes of the initial superp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…Rydberg states of atoms and molecules represent ideal model systems with which to perform detailed studies of electric field ionization, and develop schemes with which to manipulate and control ionization processes [1]. Precise measurements of ionization dynamics and electricfield ionization rates of Rydberg states are of interest in the optimization of schemes for quantum-stateselective detection [2].…”
Section: Introductionmentioning
confidence: 99%
“…Rydberg states of atoms and molecules represent ideal model systems with which to perform detailed studies of electric field ionization, and develop schemes with which to manipulate and control ionization processes [1]. Precise measurements of ionization dynamics and electricfield ionization rates of Rydberg states are of interest in the optimization of schemes for quantum-stateselective detection [2].…”
Section: Introductionmentioning
confidence: 99%
“…We calculate ionization rates using a semi-empirical formula rather than directly from the couplings to free states. In Feynman, et al essentially the same model was unable to correctly account for the phase evolution near ionization [28]. Second, a significant advantage of the GA is that it automatically takes into account uncharacterized experimental conditions, such as electric and magnetic field inhomogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 2 presents state-selective field ionization (SFI) spectra recorded at n = 60. Earlier studies have shown that the field at which a given state ionizes is governed by n, the magnitude of the magnetic quantum number |M L |, and the slew rate of the applied field [28][29][30]. Briefly, for a hydrogen atom, the ionization threshold depends on the orientation of the atomic dipole moment which is defined by the electric quantum number, k. The extreme red-shifted states within a given Stark n manifold for which k ∼ −n ionize at the smallest fields, given by ∼ 1/(9n 4 ), because their electronic wave functions are polarized towards the saddle point in the electron potential that results from application of the external field.…”
Section: State-selective Field Ionization Spectramentioning
confidence: 99%